2018
DOI: 10.1007/s00128-018-2301-0
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metals Bioavailability Approach in Intertidal Estuarine Sediments and Bioaccumulation in Associated Nereidid Polychaetes

Abstract: Polychaetes that inhabit the sediments of estuaries are important prey to many species all around the world. Laeonereis acuta is a deposit feeder living in estuaries along the Atlantic coast of South America. Ragworms accumulate metals from the sediment, and represent a means of entry of sediment contaminants into the trophic network. The concentrations of Zn, Pb, Cu, Cr and Cd were determined in polychaetes and sediments (total and extractable) from six estuarine beaches of Río de la Plata. The associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…A higher concentration of Cu can be found in lakes, rivers and estuaries than in the ocean (Georgopoulos et al, 2001). Sediments with up to 135 μg g −1 dry weight concentrations of Cu in Montevideo Bay are considered to be highly polluted (Muniz et al, 2004a), and Cu was also found in the intertidal sediments (Castiglioni et al, 2018;García-Alonso et al, 2017). The external area of Rio de la Plata estuary also has levels of Cu that could toxic for the resident biota (Carsen et al, 2003).…”
Section: Spatial Segregation Of Trophic Habits and Differential Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…A higher concentration of Cu can be found in lakes, rivers and estuaries than in the ocean (Georgopoulos et al, 2001). Sediments with up to 135 μg g −1 dry weight concentrations of Cu in Montevideo Bay are considered to be highly polluted (Muniz et al, 2004a), and Cu was also found in the intertidal sediments (Castiglioni et al, 2018;García-Alonso et al, 2017). The external area of Rio de la Plata estuary also has levels of Cu that could toxic for the resident biota (Carsen et al, 2003).…”
Section: Spatial Segregation Of Trophic Habits and Differential Exposurementioning
confidence: 99%
“…Previous research has found high concentrations of trace elements in water and sediments of the region, with historical increases associated with industrialization and urbanization processes of two important capitals, Montevideo (Uruguay) and Buenos Aires (Argentina) (Carsen et al, 2003;García-Rodríguez et al, 2010;Gil et al, 1999;Marcovecchio and Ferrer, 2005;Viana et al, 2005). Even more selective metals are bioaccumulated in polychaetes in urban coastal areas, which can be the entrance of bioavailable metals to coastal trophic networks (Castiglioni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium and Hg are among the most widespread metals in the environment and in the group of non-essential and highly toxic metals (Selvi et al, 2019). The presence of high levels in the environment is worrying, as these metals have bioaccumulation capacity that can lead to contamination of polychaetes (Castiglioni et al, 2018), fish (Amirah et al, 2013;Bosch et al, 2016), birds (Hosseini et al, 2013), and even humans (Bosch et al, 2016). The fishing activity reinforces the risk to human beings in our study area (Brasil, 2010).…”
Section: Indexesmentioning
confidence: 66%
“…Se ha trabajado mucho a nivel de comunidades bentónicas y su relación con variables ambientales, incluyendo el impacto antrópico. Los poliquetos en particular no han sido objeto de estudios específicos, aunque muchos resultados muestran a estos organismos como los presentes en sitios impactados, mostrando alto grado de tolerancia (Borthagaray et al 2006;Bergamino et al 2008;Castiglioni et al 2018).…”
Section: Atlántico Sudamericanounclassified